California exposures eaudiobook Envisioning myth and history. - White, Richard (HighBridge Audio, 2020)
"This is the West, sir. When the legend becomes fact, print the legend." This indelible quote from The Man Who Shot Liberty Valance applies especially well to California, where legend has so thoroughly become fact that it is visible in everyday landscapes. Our foremost historian of the West, Richard White, never content to "print the legend," collaborates here with his son, a talented photographer, in excavating the layers of legend built into California's landscapes. Together they expose the bedrock of the past, and the history they uncover is astonishing. Jesse White's evocative photographs illustrate the sites of Richard's historical investigations. A quiet riverside park in the Tulare Lake Basin belies scenes of horror from when settlers in the 1850s transformed native homelands into American property. Near the lake bed stands a small marker commemorating the Mussel Slough massacre, the culmination of a violent struggle over land titles between local farmers and the Southern Pacific Railroad in the 1870s. Tulare is today a fertile agricultural county, but its population is poor and unhealthy. The California Dream lives elsewhere. The lake itself disappeared when tributary rivers were rerouted to deliver government-subsidized water to big agriculture and cities. But climate change ensures that it will be back-the only question is when.